Mutual fund portfolio trading and investor flow - Dubofsky, David A. (Journal of Banking & Finance, 2010)
I estimate the extent to which mutual fund portfolio trading of securities is triggered by investor flows into and out of the funds, and find that this liquidity-induced portfolio trading activity is smaller than previously estimated by Edelen (1999). I obtain estimates from a much larger and broader sample of funds than Edelen’s (1999) sample. Portfolio managers of international funds trade a smaller fraction of investor flow than do those of domestic funds. Index funds invest a larger fraction. A funds’ usage of futures contracts does not have a statistically significant effect on how it trades in response to investor flows, but the unpredictability of investor flow weakly affects the trading response to flow.